Tibial deformities caused by focal fibrocartilaginous dysplasia: a narrative review - Fasel, Dimitri; Paris, Elio; Aye, Victor; Pilloux, Maxime; De Marco, Giacomo; Vazquez, Oscar; Steiger, Christina; Dayer, Romain; Gavira, Nathaly; Ceroni, Dimitri (Frontiers in Pediatrics, 2025)
Focal fibrocartilaginous dysplasia (FFCD) of the tibia is a rare but well-recognised, “tumour-like” condition that primarily involves the proximal tibia and causes tibial deformities. Tibial FFCD affects infants and toddlers, and deformations are typically discovered when they begin to walk. The exact aetiology of FFCD remains unclear, even though several pathophysiological hypotheses have been proposed. It is thought that FFCD's natural course is towards spontaneous resolution within a few months or years, although there is occasionally some initial worsening before the correction begins. FFCD's radiographical appearance is so explicit and pathognomonic that no biopsy is required. Conservative management is considered the gold standard treatment for this condition. However, if the deformity worsens, persists over a longer period or is severe enough (greater than 30°), then surgical treatment may be indicated. This narrative review summarises more than 40 years of observations of patients with tibial FFCD, discusses its aetiology and revises information on its pathogenesis, clinical features, radiographical and histological characteristics, and treatment.